النظام القانوني للعطل في الجزائر - معيوف العربي - رقيق حمزة (جامعة المسيلة, 2021)
هدفت هذه الدراسة إلى التعرف على النظام القانوني للعطل في الجزائر، حيث أنها تعتبر من بين اهم الحقوق التي يتمتع بها الموظف، فهي تمسه وتؤثر عليه تأثيرا بالغا من نواح عدة، يتصل بعضها بالجوانب النفسية والصحية والنفسية للموظف ولعائلته. وقد أكد المشرع الجزائري على غرار التشريعات الأخرى على عدد من العطل منها العطل مدفوعة الاجر ومنها الغير ماجورة. الكلمات المفتاحية:العطل ( الراحة، الاجازة)، الموظف، التوظيف . Abstract This study aimed to identify the legal system of holidays in Algeria, as it is considered among the most important rights enjoyed by the employee, as it affects him and affects him greatly in many ways, some of which are related to the psychological, health and psychological aspects of the employee and his family. The Algerian legislator, like other legislation, has emphasized a number of holidays, including paid holidays and unpaid ones. Keywords: holidays (rest, vacation), employee, employment.
Keywords: العطل ( الراحة، الاجازة)، الموظف، التوظيف